2014
DOI: 10.1017/s1755267214000037
|View full text |Cite
|
Sign up to set email alerts
|

Black scorpionfish Scorpaena porcus (Scorpaenidae): a first record in the eastern English Channel

Abstract: This is the first record of the black scorpionfish Scorpaena porcus being found in the eastern English Channel. A specimen was caught on 15 October 2012 off the port of Courseulles-sur-mer. It measured 31.6 cm and weighted 800 g. From a study of its sagittal otolith, this specimen appeared to be 9 years old.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Unfortunately, this representation does not consider the species that are not in the area but could arrive due to changing conditions, and can potentially deteriorate ecosystems (Occhipinti‐Ambrogi, 2007). Empirical evidences demonstrated large movements of indigenous and non‐indigenous species in the area: an abrupt northward shift of small pelagics from the Eastern English Channel to the North Sea occurred in the middle of the 1990 s, partly due to climate conditions (McLean et al, 2018), while for the first time Mediterranean species were recently recorded in the Eastern English Channel (Mahé et al, 2012, 2014), and a tropical species was recorded in the North Sea (Cresson et al, 2017). In general, stocks with smaller body size and faster life history characteristics will better adapt to warming (Free et al, 2019; Moullec et al, 2019; Perry et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this representation does not consider the species that are not in the area but could arrive due to changing conditions, and can potentially deteriorate ecosystems (Occhipinti‐Ambrogi, 2007). Empirical evidences demonstrated large movements of indigenous and non‐indigenous species in the area: an abrupt northward shift of small pelagics from the Eastern English Channel to the North Sea occurred in the middle of the 1990 s, partly due to climate conditions (McLean et al, 2018), while for the first time Mediterranean species were recently recorded in the Eastern English Channel (Mahé et al, 2012, 2014), and a tropical species was recorded in the North Sea (Cresson et al, 2017). In general, stocks with smaller body size and faster life history characteristics will better adapt to warming (Free et al, 2019; Moullec et al, 2019; Perry et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, S. porcus can be confused with other Scorpaena species in terms of both coloration and morphological characters. S. porcus was known as the black scorpionfish, but in a study conducted in the eastern English Channel, a sample of a red-colored fish was reported to be molecularly S. porcus species (Mahé et al, 2014). Besides, there were overlaps in dorsal fin rays and morphometric features of Scorpaena species (Akalın et al, 2011;Froese and Pauly, 2021), and these overlaps were more common in juvenile samples (Akalın et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, D. parini was not observed before in the North Sea, suggesting that it is not established but may migrate away from the boundary of its habitat, as a response to change in environmental conditions (Rose, 2005). This hypothesis was previously proposed to explain captures of Mediterranean species in the English Channel (Mahé et al, 2012(Mahé et al, , 2014.…”
mentioning
confidence: 94%